REGIONAL ECONOMIC DIVERSIFICATION AS A KEY FACTOR OF SUSTAINABLE GROWTH - Ismatov Fazliddin Ibodovich (Journal of Applied Science and Social Science, 2026)
This article provides a theoretical and practical analysis of the role of regional economic diversification in ensuring sustainable economic growth. In the context of global economic instability and high dependence of regions on specific sectors, balancing the economic structure emerges as a strategic necessity. The main objective of the study is to identify the relationship between the level of diversification and indicators of sustainable growth. The research applies a systematic approach, structural-dynamic analysis, and evaluation methods based on economic concentration indicators. The results demonstrate that a balanced distribution of economic activity across sectors enhances regional resilience to external shocks, improves the investment climate, and establishes a solid foundation for long-term sustainable development. The article also substantiates priority directions for improving regional economic policy.